PENGEMBANGAN WISATA RAMAH LINGKUNGAN PADA WARISAN DUNIA DAERAH ALIRAN SUNGAI (DAS) PAKERISAN DI KABUPATEN GIANYAR PROVINSI BALI - Kadek Edi Palguna; I Wayan Pramana Eka Putra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The current development of Bali tourism in some places it seems to cause some problems such as congestion, overcrowding and other social problems. Anticipating these problems, it is necessary to create new options to provide new tourist attractions. One of them is developing eco-friendly tourism in the Pakerisan watershed which has various potentials, both in terms of culture and natural beauty. The purpose of this study is to find out how the development of environmentally friendly tourism in the Pakerisan watershed, both in the utilization and conservation efforts of the object area. The research method was carried out through the stages of data collection, data processing with qualitative and comparative analysis, and descriptive data presentation. The results showed that the Pakerisan watershed has the potential as a cultural and natural tourism object. Efforts to utilize the Pakerisan watershed in environmentally friendly sustainable tourism can be carried out by implementing local philosophy and managing waste properly.Keywords:, Eco Tourism; World Heritage; Pakerisan Watershed.